Another Introduction to Islam: The Myth of the Value-Free Study of Religion (American Journal of Islam and Society, 1998)
“ . . . a form of secular intellectual arrogance which, even while itcannot claim absolute certainty for a particular hypothesis, deemsits findings superior to the content of religious truth.” (p. 267)David Waines, Introduction to Islam (Cambridge: Cambridge UniversityPress, 1995). x + 332 pp. (hardback).Following the recent events in the Muslim world, bookshops havebeen flooded by works on the subject of Islam. On examination, itbecomes clear that very few authors are willing, or indeed able, to writeabout the cultural phenomenon of the Islamic religion. Waines showswith his Introduction to Islam that he is one of those few. The approachtaken in the book raises important methodological issues for the study ofIslam and religion in general. Waines’s phenomenological approach raisesdoubt about the validity of a purely secular account of Islam whichattempts to be “value-free.” The author is on the right track in terms of asocial anthropological perspective in saying, “Religion is not a thing, buta happening, and it is people who make things happen.” This reminds thereader that Islam too has to be understood within its social and historicalmanifestations.In general, Waines portrays Islam in accordance with the phenomenologicalapproach, from the traditional Muslim standpoint, and leaves thereaders to judge Islam for themselves. In the introduction he states “Itseemed more appropriate to present the Qur’an and the ProphetMohammed as Muslims might recognize them, rather than as othershave described them.” It is in this approach that he generally breaks with ...